APRA: Letters, intellectuals and exile: About the book The revolutionary excess. Culture and politics in the origins of APRA by Martín Bergel - Gonzales Alvarado, Osmar (2020)
The Argentine historian Martín Bergel has dedicated a large part of his work as a researcher to studying Peruvian APRA, especially —but not only— in its nascent moment. This interest has been expressed in articles presented and published in academic meetings and journals in various countries; now they have been collected in this volume: Revolutionary Excess. Culture and politics in the origins of APRA (Lima: La Siniestra Essays, 2019). The interested researcher or reader has at hand a substantial source to rethink the most important political party in Peruvian history in all its complexity.